Structural examination of the interface between Au catalysts and Ge(1 1 1). (15th May 2015) - Zitouni, H.; Mehdaoui, A.; Spiesser, A.; Khodja, K. Driss; Josien, L.; Le Thanh, V.; Pirri, C.
Abstract: We investigate the interface between Au catalysts and a Ge(1 1 1) substrate. This system is achieved by dewetting an Au layer above the Au–Ge eutectic temperature. We show by high resolution transmission electron microscopy that a large amount of Ge can be moved over a surface of Ge(1 1 1) by using assistance of eutectic Au–Ge droplets. This localization is achieved thanks to the ability of nano Au–Ge droplets to incorporate a large amount of Ge and to release it by cooling down the sample at room temperature. This makes the localization process irreversible with respect to annealing at a very high temperature. The extra Ge supplied by precipitation is in epitaxy with the Ge(1 1 1) substrate. This reflects in macroscopic I ( V ) measurements.